2001
DOI: 10.1097/00006254-200110000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Third Degree Perineal Ruptures During Delivery

Abstract: Objective To determine risk factors for the occurrence of third degree perineal tears during vaginal delivery. Design A population-based observational study. Population All 284,783 vaginal deliveries in 1994 and 1995 recorded in the Dutch National Obstetric Database were included in the study. Methods Third degree perineal rupture was de®ned as any rupture involving the anal sphincter muscles. Logistic regression analysis was used to assess risk factors. Main outcome measures An overall rate of third degree pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(84 citation statements)
references
References 13 publications
9
74
1
Order By: Relevance
“…It may be difficult to prevent these complications. Although there is evidence that a prophylactic mediolateral episiotomy may prevent third-degree perineal tears in a general obstetric population (20), EDS patients may have slow and complicated healing of the episiotomy wound. Also, because of the laxity of the perineal tissue, an episiotomy may even be indicated less often than in nonaffected women.…”
Section: Discussionmentioning
confidence: 98%
“…It may be difficult to prevent these complications. Although there is evidence that a prophylactic mediolateral episiotomy may prevent third-degree perineal tears in a general obstetric population (20), EDS patients may have slow and complicated healing of the episiotomy wound. Also, because of the laxity of the perineal tissue, an episiotomy may even be indicated less often than in nonaffected women.…”
Section: Discussionmentioning
confidence: 98%
“…We focused on primiparous women, as earlier studies had concluded that birth order and a perineal tear in an earlier birth are important risk factors. [20][21][22][23][24][25][26] Excluding NHS Trusts with poor data quality may have introduced bias, as the risk-adjusted tear rates at these hospitals may be different from the rates observed in hospitals with better data quality. However, the effect size of selection bias is likely to be small because the distributions of outcome and risk factors in both groups were similar (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…39 Mode of delivery is a key determinant of the risk of perineal tears, with studies consistently demonstrating that women with instrumental deliveries have higher rates of anal sphincter tears, 2,23,28,37 and that forceps deliveries carry the highest risk of third-or fourth-degree perineal tears. The risk of having a severe perineal injury has been reported to be 1.5-14.0 times higher with forceps, and up to four times higher with ventouse, than with spontaneous vaginal delivery.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…However, the number of women (22) in this study delivered by forceps or vacuum extraction is too low to draw any conclusions on the rate of anal sphincter tears in operative vaginal delivery. We do underline, however, the statement of Murphy et al 1 that operative vaginal delivery is associated with an increased risk for anal sphincter injury, 5 but this was not the primary aim of this study.…”
Section: Sirmentioning
confidence: 72%